Prostaglandin analogs regimen for open-angle glaucoma or hypertensive ocular, is it still effective nowadays?: a systematic review: Poster Presentation - Observational Study - General practitioner - Tikha, Fidya Ainun; Rahadi, Aditia Rizka (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Open-angle glaucoma and hypertensive ocular therapy are still developing. There are new medications that offer fast and safe in lowering intraocular pressure. Prostaglandin analogs regimenis a well-known medication that we use in lowering intraocular pressure and still use in this era. Methods : A literature search was performed in PubMed, Chocraine, and Google Scholar for studies that fit our inclusion criteria. The Literature must be Randomized controlled trials, Systematic reviews, and meta-analyses from 2013 until 2023 that report data on prostaglandin analogs regimen uses medications for open-angle glaucoma or ocular hypertension. That consists of data on intraocular pressure (IOP) lowering effect by the use of prostaglandin analogs regimen monotherapy or combination. Results : We included Ten literature that consists 5 RCTs (1514 participants), and 5 systematic reviews with meta-analysis (235 RCT literature), that overall make intraocular pressure (IOP) reduction. There are differences in duration to reduce IOP between prostaglandin analogs regimen types and combinations with other classes of regimen. Conclusion : prostaglandin analogs regimen effective in IOP lowering effect in open-angle glaucoma and hypertensive ocular both monotherapy and combination.